Gallstone abscess as a result of dropped gallstones during laparoscopic cholecystectomy - Singh, Kuldeep (Elsevier, 2012)
INTRODUCTION: With the advent of laparoscopic cholecystectomy we have seen a “disease of medical progress” (DOMP). Herein we report a complication that developed 7 years after laparoscopic cholecystectomy. PRESENTATION OF CASE: A 42 year old woman presented with worsening right-sided pain and tenderness. Seven years prior she underwent a laparoscopic cholecystectomy. Computed tomography demonstrated a subhepatic retroperitoneal inflammatory mass. On open exploration a 4 cm × 6 cm retroperitoneal mass was excised. The mass contained purulent material and gallstones. DISCUSSION: Laparoscopic cholecystectomy has become the “gold standard” for the treatment of symptomatic gallstones. Prior to laparoscopic cholecystectomy there was no body of literature about lost gallstones thus making this a DOMP. In contrast, it is reported that as many as 5.4–19% of laparoscopic cholecystectomies have stones spilled with variable rates of retrieval. Our case demonstrates an extreme example of a complication resulting seven years after a laparoscopic cholecystectomy with gallstones left behind. CONCLUSION: Recognizing that gallstones will be lost during some cases of laparoscopic cholecystectomy, we must remain vigilant and make a full attempt to retrieve all stones to prevent such rare but not insignificant potential complications.